RELATIONSHIP BETWEEN AGE AND BATHEL INDEX OF ISCHEMIC STROKE PATIENTS IN STROKE UNIT OF RSUP DR. SARDJITO, YOGYAKARTA - , JEYA PRASAD NAIR JEYA BALU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Stroke is on par with cerebrovascular disease as the third silent killer disease after coronary heart disease and tuberculosis. Stroke has been associated for the 5.7 million deaths worldwide, equivalent to 9,9 % of all deaths. World Health Organization (WHO) has defined stroke as a focal (or at times global) neurological impairment of sudden onset, and lasting more than 24 hours (or leading to death), and of presumed vascular origin. Objective: To identify the relationship between age of patient in admission and the outcome of stroke scored by Modified Barthel Index in acute ischemic stroke patient. Method: We use cross-sectional study with stroke patient in unit stroke throughout the year 2012 as the samples. The data were gathered from medical report of stroke unit in Dr. Sardjito hospital with number of sample 66 patients. Data gathered were age of patient when admitted to Stroke Unit, Modified Barthel Index score, and some of confounding factors. The analysis was done by testing the association between variable groups using chi-square test. Result: Chi-Square test showed that there is no significance differences between patients with higher age group and stroke severity scored by Modified Barthel Index score with p-value = 0,313. Conclusion: No significance difference between outcome of stroke in patient of group â¤50 years of age and in patient of group >50 years of age in acute ischemic stroke patients in Dr. Sardjito Hospital.